Ecdysteroids and spirosterane steroids from the traditional Chinese medicine Paris polyphylla var. yunnanensis. (October 2021) - Guo, Kai; Ren, Xue; Mu, Rong-Fang; Zhou, Ting-Ting; Li, Dan; Hu, Hong; Liu, Yan; Li, Sheng-Hong
Graphical abstract: Highlights: Six steroids were found from the rhizomes of Paris polyphylla var. yunnanensis . Two new ecdysteroids were first discovered in this study. The steroids were inactive in the immunosuppressive and anti-adipogenesis assay. Abstract: Phytochemical investigation of the rhizomes of Paris polyphylla var. yunnanensis led to the isolation of four ecdysteroids (1 −4 ) including two new ecdysteroids (1 −2 ), and two known spirostane steroids (5 −6 ). Their structures were elucidated by extensive spectroscopic analyses as well as comparisons with those reported in the literature. All the isolates were assayed for their immunosuppressive and adipogenesis inhibitory activities but were inactive.